2017
DOI: 10.1186/s13620-017-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

A survey of free-ranging deer in Ireland for serological evidence of exposure to bovine viral diarrhoea virus, bovine herpes virus-1, bluetongue virus and Schmallenberg virus

Abstract: BackgroundDeer are an important wildlife species in both the Republic of Ireland and Northern Ireland having colonised most regions across the island of Ireland. In comparison to cattle and sheep which represent the main farmed ruminant species on the island, there is a lack of data concerning their exposure, as measured by the presence of antibodies, to important viral pathogens of ruminants. A study was therefore undertaken to investigate the seroprevalence of wild deer to four viruses, namely bovine viral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
(80 reference statements)
0
21
2
Order By: Relevance
“…In addition, the occurrence of diarrhea may also have a viral cause, such as Bovine viral diarrhea virus (BVDV). It has been reported that BVDV does not possess strict host-specificity and infections of over 50 species in the mammalian ( Passler et al, 2016 ; Graham et al, 2017 ). But the 16S-rRNA gene sequencing can’t detect viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the occurrence of diarrhea may also have a viral cause, such as Bovine viral diarrhea virus (BVDV). It has been reported that BVDV does not possess strict host-specificity and infections of over 50 species in the mammalian ( Passler et al, 2016 ; Graham et al, 2017 ). But the 16S-rRNA gene sequencing can’t detect viruses.…”
Section: Discussionmentioning
confidence: 99%
“…An eradication campaign against BVDV (Pestivirus A and B) has been enforced in Germany since 2011 and it is considered to be in the final stage of eradication (60). However, screenings for BVDV antibodies in wild ruminants in Europe reported the incidental spillover of the virus from cattle to cervids (28,61). The detection of antibodies against pestivirus in reindeer in this study (4.2%) indicates the exposure to a virus from this genus in the captive reindeer in Germany.…”
Section: Discussionmentioning
confidence: 61%
“…Serological screenings have demonstrated the presence of antibodies against SBV in a variety of wild ruminants in Europe (28). However, serological screening of 187 wild (2010-2013) and 450 semi-domesticated reindeer (2013-2015) in Norway, and 635 semi-domesticated reindeer in Finland, all R. t. tarandus, revealed no antibodies against SBV (30) and, to our knowledge, there are no reports on SBV in reindeer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations